PENANAMAN NILAI SOSIAL MATA PELAJARAN IPS TERPADU MENGGUNAKAN MODEL PICTURE AND PICTURE DAN EXAMPLES NON EXAMPLES - Hayatu Rizki; Eddy Purnomo; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This study aims to determine whether there are differences social value of planting Integrated social studies using picture and picture examples and non examples with respect to interest in learning. Population 170 students and sample 80 students. Quasi-experimental research methods. Data was collected through observation, interviews and questionnaires. Hypothesis testing using two-way analysis of variance and t-test two independent samples. Results showed (1) first hypothesis testing is known to have differences in social value teaching students who are taught using picture and picture and students who were taught using examples non examples. (2) second hypothesis testing known cultivation of social value students who have high interest in learning who are taught to use picture and picture is higher than that was taught using examples non examples. (3) third hypothesis testing known cultivation of social value students who have  high interest in learning who are taught to use picture and picture is higher than that was taught using examples non examples. (4) fourth hypothesis testing found no interaction between of learning with social studies learning interest towards planting Integrated social value. kata kunci: ene, pap, nilai sosial.